Solution :-
=> - 7 ( x + 1 ) - 3 = - 8x + 11
=> - 7x + ( - 7 ) - 3 = - 8x + 11
=> - 7x - 7 - 3 = - 8x + 11
=> - 7x - 10 = - 8x + 11
By putting the the variable terms on one side & constant terms on the other side we have ,
=> - 7x + 8x = 11 + 10 ....eq( 1 )
=> x = 21
Hence , x = 21
Verification :-
By substituting the value of x we got in the above solution . If LHS = RHS we have ,
➩ - 7 ( 21 ) + 8 ( 21 ) = 11 + 10
By taking common in RHS
➩ ( 21 ) ( - 7 + 8 ) = 11 + 10
➩ 21 × 1 = 21
➩ 21 = 21
LHS = RHS
Hence , verified